Influence of resveratrol release on the tissue response to mechanically adaptive cortical implants. (1st January 2016) - Nguyen, Jessica K.; Jorfi, Mehdi; Buchanan, Kelly L.; Park, Daniel J.; Foster, E. Johan; Tyler, Dustin J.; Rowan, Stuart J.; Weder, Christoph; Capadona, Jeffrey R.
Graphical abstract: Abstract: The stability and longevity of recordings obtained from intracortical microelectrodes continues to remain an area of concern for neural interfacing applications. The limited longevity of microelectrode performance has been associated with the integrity of the blood brain barrier (BBB) and the neuroinflammatory response to the microelectrode. Here, we report the investigation of an additive approach that targets both mechanical and chemical factors believed to contribute to chronic BBB instability and the neuroinflammatory response associated with implanted intracortical microelectrodes. The implants investigated were based on a mechanically adaptive, compliant nanocomposite (NC), which reduces the tissue response and tissue strain. This material was doped with various concentrations of the antioxidant resveratrol with the objective of local and rapid delivery. In vitro analysis of resveratrol release, antioxidant activity, and cytotoxicity suggested that a resveratrol content of 0.01% was optimal for in vivo assessment. Thus, probes made from the neat NC reference and probes containing resveratrol (NC Res) were implanted into the cortical tissue of rats for up to sixteen weeks. Histochemical analysis suggested that at three days post-implantation, neither materials nor therapeutic approaches (independently or in combination) could alter the initial wound healing response. However, at two weeks post-implantation, the NC Res implant showed a reduction in activated microglia/macrophages and improvement in neuron density at the tissue-implant interface when compared to the neat NC reference. However, sixteen weeks post-implantation, when the antioxidant was exhausted, NC Res and the neat NC reference exhibited similar tissue responses. The data show that NC Res provides short-term, short-lived benefits due to the antioxidant release, and a long-term reduction in neuroinflammation on account of is mechanical adaptive, compliant nature. Together, these results demonstrate that local delivery of resveratrol can provide an additive advantage by providing a consistent reduction in the tissue response.